Buyer Power and Innovation of Quality Products: Empirical Evidence from the German Food Sector. - Christoph R. Weiss; Antje Wittkopp (Kiel University, Department of Food Economics and Consumption Studies, 2003)
The last couple of decades have seen an increased retail concentration around the world, particularly in Europe. Views on the welfare implications of this severe change are controversial. Consumers might benefit because larger stores (owned by larger retailer chains) offer more product choices. On the other hand, there is concern that buyer power may force manufacturers "to reduce investment in new products or product improvements" [1]. This paper's aim is to analyse whether retailer power affects food manufacturing firms incentives to invest in innovation of high quality food products. On the basis of a formal model, we find that retailer market power reduces upstream firms incentives to introduce new products. This proposition is tested empirically on the basis of firm level data from a survey of food manufacturing firms carried out in 2002 in Germany. Results of multinomial logit model show a moderate and negative impact of retailer market power on innovation of regular quality products. No such negative impact is observed for premium quality products. Producers of premium products thus seem to more effectively resist retailer market power in product innovation.
Keywords: 330; Retailer market power; innovation; product quality; multinomial logit model; Lebensmitteleinzelhandel; Nachfragemacht; Innovation; Produktqualität; Nahrungsmittelgewerbe; Wirtschaftskonzentration; Schätzung; Deutschland